Existential well-being predicts psychopathy traits in Tunisian college students. Issue 7 (8th August 2020) - Fekih-Romdhane, Feten; Ben Hamouda, Abir; Khemakhem, Rania; Halayem, Soumeyya; BelHadj, Ahlem; Cheour, Majda
ABSTRACT: Despite the growing interest in researching predictive factors of psychopathic traits in non-criminal samples, little is known about their implications for everyday functioning, such as religious or spiritual beliefs. We aimed to analyze the relationship between psychopathic traits and religiosity and spiritual well-being. We carried out a cross-sectional study of 516 university students enrolled at three major Tunisian universities. The Levenson Self-Report Psychopathy Scale, the Spiritual Well-Being Scale and the Arabic Religiosity Scale were used. Results from the multivariate linear regression analysis found that after controlling for demographic variables and substance use, existential wellbeing represented the only religious or spiritual variable among the significant predictors in the final model and explained 3.8% of the variance in psychopathy. Psychopathy prevention programmes should include an educational component that teaches young people certain values and human qualities such as altruism, selfless giving, openness to others, and the ability to discover meaning and purpose in life.